Kemampuan Representasi Matematis Siswa Kelas VIII SMP Ditinjau dari Gaya Kognitif Visualizer dan Verbalizer - Fergi Faranijza Fatri; Maison Maison; Syaiful Syaiful (Didaktik Matematika, 2019)
Mathematical representation skill is students' ability to express mathematical ideas (such as problems, statements, and definitions) in various ways to solve problems through multiple representations, such as images, words, tables, and symbols mathematics. Students are struggling in representing mathematical ideas. It hampers them in determining the solution of mathematical problems. They are careless in reading the word problems, lacking problem analysis, less thorough, and struggling to connect concepts. The subjects of this study were in two students from one of the junior high school in Jambi. The instruments used for this research were VVQ, Mathematical Representation Ability Test and interviews. This study used a descriptive qualitative method. The results showed that the representation abilities of students with visualizer and verbalizer style were quite good. However, each subject had a different way of solving problems. Visualizers were more interested in questions with image information in solving the problem. Verbalizer tended to prefer information with detailed wording.